Determinants of inflation on the economy of Asean - Chong, Xin Yi (2023)
This paper focused on the determinants that would bring impact to the inflation on ASEAN countries’ economy including Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, and Vietnam. In the meantime, this paper also investigated the relationship between the dependent variable which is inflation and each factor that influencing the inflation for ASEAN countries. Factors consist of interest rate, nominal wage, unemployment rate, money supply, and crude oil. In order to investigate the determinants of inflation on ASEAN countries’ economy, the panel data analysis will be tested by using the panel unit root test which included Augmented Dickey-Fuller (ADF) test, and Phillips-Perron (PP) test. After that, the Pooled Ordinary Least Square (POLS), Fixed Effects Model (FEM), and Random Effects Model (REM) were caried out as well. Hausman Test, Poolability F-Test, and Breusch-Pegan Lagrange Multiplier Test (LM) were applied to select the best estimated model. The diagnostic checking performed as well in order to detect any underlying economic problems under the model.